Do maternal cells trigger or perpetuate autoimmune diseases in children? - Stevens Anne M (BMC, 2007)
Abstract The placental barrier is not the impenetrable wall that it was once presumed to be. During pregnancy, fetal cells pass into the mother, where they persist for decades after the pregnancy, leading to fetal microchimerism (FMc). Maternal cells also pass into the fetus, where they can persist long after birth of the child into adulthood, leading to maternal microchimerism(MMc). FMc and MMc represent foreign cells, and thus have been implicated in the pathogenesis of autoimmune diseases that resemble graft-versus-host disease after stem cell transplantation. FMc, hypothesized to contribute to the high predisposition of autoimmune diseases in women, has been reviewed recently. In patients who have never been pregnant, (children, males, and nulliparous females), MMc may represent the foreign cells that initiate or perpetuate chronic inflammatory disease.